Analysis Of The Effect Of Service Quality, Location On Purchasing Decisions Through Sales - lutfi, sofiana; P, Ratih Hesty Utami; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study was to determine the effect of service quality, location on purchasing decisions through sales volume as an intervening variable. This study uses the Structural Equation Model Partial Least Square (SEM-PLS) method with the SmartPLS version 3.2.9 application to analyze the data. The population used in this study were people in Karangasem Sayung Demak. The sample in this study was taken using the simple Random Sampling method where the sample from the population was randomized without considering the population strata. The criteria used in this study are people and those who have bought products at PT Rocket Chiken Karangasem Sayung Demak. Based on the results of the study, it was found that Service Quality has a positive and significant effect on Purchasing Decisions, Location has a positive and significant effect on Purchasing Decisions, Purchasing Decisions have a positive and significant effect on Sales Volume, Service Quality has a positive and insignificant effect on Sales Volume, Location has a significant positive effect on Sales Volume mediated by Purchasing Decisions, Location has a positive and insignificant effect on Sales Volume which mediates the Purchasing Decision.